Serum adropin levels as a potential biomarker for predicting diabetic kidney disease progression - Chen, I-Wen; Lin, Cheng-Wei; Lin, Chia-Ni; Chen, Szu-Tah (Frontiers in Endocrinology, 2025)
BackgroundTo investigate the value of serum adropin in predicting chronic kidney disease (CKD) progression in subjects with type 2 diabetes (T2D).Materials and methodsSerum adropin levels were measured in normal control and T2D patients with various stage of CKD. CKD progression was defined as ≥ 30% decline from the baseline estimated glomerular filtration rate. Logistic regression analysis was applied to assess the association between adropin levels and CKD progression.ResultsThe study included 58 subjects with T2D (18 early CKD and 40 advanced CKD) and 9 subjects without diabetes (control). Subjects with T2D had significantly higher adropin levels than controls (6393.10 ± 1611.84 vs. 3470.30 ± 1284.41 pg/ml; P < 0.001). Meanwhile, T2D patients with advanced CKD had higher adropin levels than those with early CKD (6848.89 ± 1287.04 vs. 5380.25 ± 1826.44 pg/ml; P = 0.003). Among T2D patients, subjects experienced CKD progression had higher adropin levels than those without (7520.15 ± 843.21 vs. 6151.16 ± 1661.61 pg/mL, P =0.003). Thus, adropin predicts CKD progression in T2D patients with 86% sensitivity and 70% specificity at 6872.24 pg/ml cutoff value. The association with CKD progression was still significant after adjusting for age, gender and body mass index (adjusted odds ratio = 27.188, 95% confidence interval 1.415-522.527, P =0.029).ConclusionsThe above findings suggest that serum adropin could be applied as a potential biomarker for predicting CKD progression in subjects with T2D. Further research is needed to validate these results and explore the underlying mechanisms.